An investigation into a driver-to-driver communication device to manage and improve the interaction between drivers - de Souza Lamas, Jose Raphael (2018)
Drivers must communicate with other road users to make their intentions clear, thereby enhancing the quality of the driving experience, improving safety on the roads and avoiding accidents. This interaction can be made either formally using legal signals approved by legislative bodies (e.g. use of indicators), or informally (e.g. hand gestures). However, this informal interaction may not be clearly understood by all drivers, and may lead to stress, strong emotional responses or aggressive driving behaviour. Moreover, a single informal interaction, e.g. flashing the headlights, can have several different meanings such as “Your headlights are on”, “Thank you”, or “I want to overtake you”, depending on the situation. Driver interaction could be enhanced by an electronic driver-to-driver communication device (DDCD), which would allow motorists to exchange messages with each other. The technology associated with connected vehicles could be used for the design of this communication device. For example, wireless devices and sensors already allow vehicles to exchange information with other vehicles (V2V) and road infrastructure (V2I) at any time.